Linking Inflammation to Natural Killer T Cell Activation - Salio, Mariolina (Public Library of Science, 2009)
Immune activation is often associated with inflammation, but inflammation's role in the expansion of antigen-specific immune responses remains unclear. This primer focuses on recent findings that show how specific natural killer T cells are activated by inflammatory messengers, thus illuminating the cellular and molecular links between immunity and inflammation.